Effect of electron radiation on small-signal parameters of NMOS devices at mm-wave frequencies. (April 2020) - Habeenzu, Brilliant; Meyer, Walter; Stander, Tinus
Abstract: The effect of electron radiation on the forward-active small-signal model parameters for 0.35 μm CMOS devices is reported. Four devices with different gate widths were exposed to electron radiation using a Strontium 90 (Sr 90) radiation source at dose rates of 200 kRad (Si)/hr up to a total radiation dose of 2.7 MRad. S-parameters were measured, and small-signal models extracted, both pre-irradiation and at regular dose intervals. Relationships between small-signal model parameters and total radiation dose d were derived and used to calculate small-signal parameters. The major model variations due to total ionizing dose exposure were increases in the gate resistance ( R g ), gate drain capacitance ( C gd ) and gate source capacitance ( C gs ), with a reduction in transconductances ( g m and g ds ). This results in S11 and S22 becoming more resistive as d is increased, with a decrease in the unilateral gain, f T and f max . The application of the data in predictive modelling of radiation damage is demonstrated.